COGNITION AND INCOME IN OLD AGE. (11th November 2018) - Aguila, E; Casanova, M
Abstract: We investigate whether an intervention providing old age individuals with supplemental income in the Yucatan state of Mexico was successful at improving cognitive performance. This program differed from a similar one implemented nationally in the size of the transfer (smaller) and target population (more urban). Using data from a randomized control trial (N=1015), we estimate the effect of the intervention on immediate and delayed word recall scores, finding the intervention improved both scores significantly for both men and women (0.25–0.50 standard deviations; p<0.01). To explain these findings, we analyzed a number of secondary outcomes and focus on the intervention's effect on improving health care utilization. This likely improved management of chronic conditions (like diabetes and hypertension), which are important risk factors for cognitive health. The results suggest an important pathway to improving cognitive health for individual in low income settings.